Sensitivity and adaptability of methanogens to perchlorates: Implications for life on Mars. (January 2016) - Kral, Timothy A.; Goodhart, Timothy H.; Harpool, Joshua D.; Hearnsberger, Christopher E.; McCracken, Graham L.; McSpadden, Stanley W.
Abstract: In 2008, the Mars Phoenix Lander discovered perchlorate at its landing site, and in 2012, the Curiosity rover confirmed the presence of perchlorate on Mars. The research reported here was designed to determine if certain methanogens could grow in the presence of three different perchlorate salt solutions. The methanogens tested were Methanothermobacter wolfeii, Methanosarcina barkeri, Methanobacterium formicicum and Methanococcus maripaludis . Media were prepared containing 0%, 0.5%, 1.0%, 2%, 5% and 10% wt/vol magnesium perchlorate, sodium perchlorate, or calcium perchlorate. Organisms were inoculated into their respective media followed by incubation at each organism׳s growth temperature. Methane production, commonly used to measure methanogen growth, was measured by gas chromatography of headspace gas samples. Methane concentrations varied with species and perchlorate salt tested. However, all four methanogens produced substantial levels of methane in the presence of up to 1.0% perchlorate, but not higher. The standard procedure for growing methanogens typically includes sodium sulfide, a reducing agent, to reduce residual molecular oxygen. However, the sodium sulfide may have been reducing the perchlorate, thus allowing for growth of the methanogens. To investigate this possibility, experiments were conducted where stainless steel nails were used instead of sodium sulfide as the reducing agent. Prior to the addition of perchlorate and inoculation, the nails were removed from the liquid medium. Just as in the prior experiments, the methanogens produced methane at comparable levels to those seen with sodium sulfide as the reductant, indicating that sodium sulfide did not reduce the perchlorate to any significant extent. Additionally, cells metabolizing in 1% perchlorate were transferred to 2%, cells metabolizing in 2% were transferred to 5%, and finally cells metabolizing in 5% were transferred to 10%. All four species produced methane at 2% and 5%, but not 10% indicating some success in adapting cells to concentrations higher than 1%. The results reported here indicate that the presence of perchlorate on Mars does not rule out the possible existence of methanogens. Highlights: Some methanogens can produce methane in the presence of a 1% perchlorate solution. Some of these methanogens were able to adapt to 5% perchlorate. Two species survived in 25% perchlorate solution for short periods of time.